The Histone Acetyltransferase CfGcn5 Regulates Growth, Development, and Pathogenicity in the Anthracnose Fungus Colletotrichum fructicola on the Tea-Oil Tree - Zhang, Shengpei; Guo, Yuan; Chen, Siqi; Li, He (Frontiers in Microbiology, 2021)
The tea-oil tree (Camellia oleifera Abel.) is a commercial edible-oil tree in China, and anthracnose commonly occurs in its plantations, causing great losses annually. We have previously revealed that CfSnf1 is essential for pathogenicity in Colletotrichum fructicola, the major pathogen of anthracnose on the tea-oil tree. Here, we identified CfGcn5 as the homolog of yeast histone acetyltransferase ScGcn5, which cooperates with ScSnf1 to modify histone H3 in Saccharomyces cerevisiae. Targeted gene deletion revealed that CfGcn5 is important in fungi growth, conidiation, and responses to environmental stresses. Pathogenicity assays indicated that CfGcn5 is essential for C. fructicola virulence both in unwounded and wounded tea-oil tree leaves. Further, we found that CfGcn5 is localized to the nucleus and this specific localization is dependent on both NLS region and HAT domain. Moreover, we provided evidence showing that the nuclear localization is essential but not sufficient for the full function of CfGcn5, and the NLS, HAT, and Bromo domains were proven to be important for normal CfGcn5 functions. Taken together, our studies not only illustrate the key functions of CfGcn5 in growth, development, and pathogenicity but also highlight the relationship between its locations with functions in C. fructicola.